ANALISIS PENGARUH KEPERCAYAAN TERHADAP MINAT MUZAKKI DALAM MENYALURKAN ZAKAT MELALUI BAZNAS KOTA BUKITTINGGI - Dhea (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study departs from the importance of the role of BAZNAS as an official zakat management institution, although the interest of muzakki to distribute zakat through BAZNAS is still influenced by trust factors, especially related to aspects of transparency, accountability, and professionalism of fund management. The purpose of this study is to examine and analyze the extent to which trust influences the interest of muzakki in paying zakat through BAZNAS Bukittinggi City. The research approach used is a quantitative method with field research. The study population includes 75 muzakki who have distributed zakat through BAZNAS Bukittinggi City. The data analyzed consists of primary and secondary data, with collection techniques including literature studies, observation, and questionnaire distribution. Data analysis was carried out using simple linear regression with the help of SPSS software. The results of the analysis show that the trust variable has a positive and significant influence on the interest of muzakki, with a regression coefficient value of 0.818, a t-value of 160.461, and a p-value <0.001. In addition, the coefficient of determination (Adjusted R²) value of 0.997 indicates that 99.7% of the variation in muzakki interest can be explained by the trust factor, while the remaining 0.3% is influenced by other